Potensi Senyawa Bioaktif Bajakah Spatholobus litoralis Hassk Sebagai Antimikroba Dengan Cara In-Vitro dan In-Silico - Alif Rahman Habibi; Eva Johannes; Sulfahri (Jurnal Ilmu Alam dan Lingkungan, 2022)
Bajakah (Spatholobus littoralis Hassk) is a plant originating from the forests of Kalimantan which contains compounds in the form of alkaloids that act as antimicrobials. The purpose of this study was to determine the activity of Spatholobus littoralis Hassk as an antibacterial. The in-silico method was carried out using a bioinformatics-based tool and antibacterial testing using the well method, this is because testing with the pitting method is more effective because the extract reacts directly with the test bacteria. Observations on S. aureus bacteria for 1x24 hours with a concentration of 12.5% formed an inhibition zone of 13.25 mm, a concentration of 25% formed an inhibitory power of 14.10 mm, and a concentration of 50% formed an inhibition zone of 15.4 mm. At 2x24 hours observation with a concentration of 12.5% formed an inhibitory zone of 13.625 mm, a concentration of 25% formed an inhibitory power of 14.50 mm, and for a concentration of 50% formed an inhibitory power of 15.70 mm. Meanwhile, E.coli bacteria do not form a clear zone so they do not have antibacterial properties.